68.8k views
4 votes
X+7y=0 2x-8y=22 with substitution

User Crawler
by
5.8k points

1 Answer

2 votes

For this case we have the following system of equations:


x + 7y = 0\\2x-8y = 22

According to the first equation we have:


x = -7y

Thus, we have the equivalent system:


x = -7y\\2x-8y = 22

Substituting the first equation in the second equation we have:


2 (-7y) -8y = 22\\-14y-8y = 22

Equal signs are added and the same sign is placed:


-22y = 22\\y = \frac {22} {- 22}\\y = -1

We look for the value of the variable x:


x = -7y\\x = -7 (-1)\\x = 7

Thus, the system solution is:
(x, y) :( 7, -1)

Answer:


(x, y) :( 7, -1)

User New Co
by
5.9k points